Newspaper „Šviesa“ - Vėbra, Rimantas (Knygotyra, 1976)
Lithuanian illegal press of the second half of the 19th century is one of the basic historical sources to study the problems of the said time.In the Lithuanian Sowjet historiography we still lack special studies devoted to an analysis of this press.In this paper the author is trying to reveal the thematic structure of this newspaper and to appraise its tactics and its ideological trend.In the pages of the newspaper there have to a certain extend found their place all the principal problems of the development of the Lithuanian society of the time: the struggle for the national market, the national movement etc.The author of this paper, on the ground of an analysis of the contents of the most important papers published in „Šviesa“, is arriving to the conclusion that in the history of the newspaper, as far as its ideological trends are concerned, there have been two periods: 1) the period from 1887 to 1888 and 2) that of 1890. In the first period the main trend of the newspaper was clearly clerical, in the second – in the most secular. As to its tactics, the newspaper „Šviesa“ is closer to the liberal clerical newspaper „Tėvynės sargas“ than to the ultraclerical „Apžvalga“.